Persistent Bradycardia with the Long-term Use of Phenytoin and Oxycodone: First Case Report - Syed, Intekhab Askari (Cureus, 2018)
Phenytoin is a medication that is used primarily in the treatment of epilepsy as well as generalized tonic-clonic seizures and status epilepticus. Phenytoin is also considered a class IB antiarrhythmic medication by shortening the duration of the action potential and increasing myocardial conduction. The neurologic adverse effects of phenytoin are well-documented and include altered mental status, ataxia, and nystagmus. Some adverse cardiac manifestations have also been reported, including arrhythmias, hypotension, and respiratory arrest. Oxycodone is an opioid that exerts its effects by binding to Mu opioid receptors located in the central nervous system. This selective binding results in the opening of potassium (k+) channels and the closing of calcium channels, decreasing synaptic transmission. Oxycodone, unlike phenytoin, has not been observed to elicit cardiotoxicity independent of other medications. However, in combination with other medications, bradycardia and hypotension have been observed. We report the case of a 62-year-old male who developed persistent bradycardia following treatment with phenytoin and oxycodone for seizure disorder and pain, respectively. To our knowledge, this is the first case report where bradycardia was induced by a combination of these medications.